2021
DOI: 10.1002/psb.1909
|View full text |Cite
|
Sign up to set email alerts
|

What can we learn from patients’ experiences of polypharmacy?

Abstract: Health professionals need to understand patients’ own experiences and the issues that are important to them in order to tackle the challenges posed by multimorbidity and polypharmacy. This article provides a summary of a recent Danish systematic review that examined multimorbid patients’ perspectives on polypharmacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…Tasks performed by patients included ordering; organising and storing medicines; 31,32 planning the taking; 33 monitoring and eventually reporting effects, reactions and interactions; and coordinating tests and appointments 34 . Our data confirmed that safe medicines self‐management requires a wide range of knowledge and skills 18,35 If we acknowledge that medicines self‐management by patients with polypharmacy implies skilled work, 33 we cannot ignore the inherent inequalities in, for example, health literacy, levels of deprivation, language barriers, 36 race and ethnicity 37 and access to social support 38 . In the United Kingdom, the COVID‐19 pandemic brought to light how race and ethnicity affect people's access to and experiences of care 39 .…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Tasks performed by patients included ordering; organising and storing medicines; 31,32 planning the taking; 33 monitoring and eventually reporting effects, reactions and interactions; and coordinating tests and appointments 34 . Our data confirmed that safe medicines self‐management requires a wide range of knowledge and skills 18,35 If we acknowledge that medicines self‐management by patients with polypharmacy implies skilled work, 33 we cannot ignore the inherent inequalities in, for example, health literacy, levels of deprivation, language barriers, 36 race and ethnicity 37 and access to social support 38 . In the United Kingdom, the COVID‐19 pandemic brought to light how race and ethnicity affect people's access to and experiences of care 39 .…”
Section: Discussionsupporting
confidence: 64%
“… 34 Our data confirmed that safe medicines self‐management requires a wide range of knowledge and skills 18 , 35 If we acknowledge that medicines self‐management by patients with polypharmacy implies skilled work, 33 we cannot ignore the inherent inequalities in, for example, health literacy, levels of deprivation, language barriers, 36 race and ethnicity 37 and access to social support. 38 In the United Kingdom, the COVID‐19 pandemic brought to light how race and ethnicity affect people's access to and experiences of care. 39 Research about how health inequalities impact on medicines self‐management experiences in the older people is still limited, 37 and interventions to support frail older people on polypharmacy should take care not to widen health inequalities.…”
Section: Discussionmentioning
confidence: 99%